Smoking Behavior of High School Students in Jambi City - Rezer, Yuni Dita; Ridwan, M; Sari, Puspita (PT FORMOSA CENDEKIA GLOBAL, 2024)
Cigarettes are addictive substances that, when used, can cause a number of adverse health effects. The objective of this study was to ascertain the proportion of schools that conduct eight assessments of smoke-free area indicators, gain insight into the role of officers, and evaluate the supervision of smoke-free area policies. This study employed a qualitative descriptive approach, utilizing in-depth interviews and focus group discussions (FGDs) as its primary methods of data collection. Purposive sampling strategy used for qualitative research, with a sample size of 17 informants. The qualitative analysis was conducted using the Open Code application. The findings of this study indicate that the majority of the school community is aware of the dangers of smoking and the No Smoking Area policy. However, the role of officers and supervision of the No Smoking Area is still not being carried out effectively. The study findings indicate that schools in Jambi City have not implemented the No Smoking Area policy.